2018
DOI: 10.1186/s13045-018-0657-6
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1-CDK4 activity drives sensitivity to bortezomib in mantle cell lymphoma by blocking autophagy-mediated proteolysis of NOXA

Abstract: BackgroundMantle cell lymphoma (MCL) is an aggressive B-non-Hodgkin lymphoma with generally poor outcome. MCL is characterized by an aberrantly high cyclin D1-driven CDK4 activity. New molecular targeted therapies such as inhibitors of the ubiquitin-proteasome system (UPS) have shown promising results in preclinical studies and MCL patients. Our previous research revealed stabilization of the short-lived pro-apoptotic NOXA as a critical determinant for sensitivity to these inhibitors. It is currently unclear h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Blocking autophagy could increase cancer cells sensitivity to chemotherapy. For instance, bortezomib-induced MCL cell death was significantly potentiated by compounds that interfered with autophagosomal function [164]. HMGB1-dependent autophagy promotes chemotherapy resistance in three ways: nuclear HMGB1 upregulates the expression of HSP27, cytoplasmic HMGB1 activates the Beclin-1/PI3K-III complex, and extracellular HMGB1 binds to RAGE [45,165].…”
Section: Autophagymentioning
confidence: 99%
“…Blocking autophagy could increase cancer cells sensitivity to chemotherapy. For instance, bortezomib-induced MCL cell death was significantly potentiated by compounds that interfered with autophagosomal function [164]. HMGB1-dependent autophagy promotes chemotherapy resistance in three ways: nuclear HMGB1 upregulates the expression of HSP27, cytoplasmic HMGB1 activates the Beclin-1/PI3K-III complex, and extracellular HMGB1 binds to RAGE [45,165].…”
Section: Autophagymentioning
confidence: 99%
“…Interestingly, CDK4/6 inhibitors might display influences on the tumor microenvironment. For instance, inhibition of CDK4 activity would significantly reduce the stabilization of autophagy-mediated proteasome NOXA and induce cell apoptosis in mantle cell lymphoma 78. Also, studies demonstrated that cyclin D-CDK4 kinase destabilized PD-L1 via Cullin3 SPOP to control cancer immune surveillance and revealed the potential combination of CDK4/6 inhibitors and PD-1/PD-L1 blockade to enhance therapeutic efficacy for human cancers 79.…”
Section: Discussionmentioning
confidence: 99%
“…By interacting with MCL-1, NOXA allows the release of the pro-apoptotic effector, BAK, leading to mitochondrial depolarization and initiation of the apoptotic cascade [101]. Interestingly, the inhibition of cyclin D1/CDK4 activity in MCL cells reduces the stabilization of NOXA, directing the protein through degradation by an autophagy mechanism [110].…”
Section: Resistance To Bortezomib and Proteasome Inhibitorsmentioning
confidence: 99%